2n-15n=26

Simple and best practice solution for 2n-15n=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n-15n=26 equation:



2n-15n=26
We move all terms to the left:
2n-15n-(26)=0
We add all the numbers together, and all the variables
-13n-26=0
We move all terms containing n to the left, all other terms to the right
-13n=26
n=26/-13
n=-2

See similar equations:

| X×(35-7x)=0 | | 9/10=10/n | | 3/5x-2=1/3+1/4x | | 2(x=5)=2+2x10 | | x2+30=27 | | 6y-(2y-5)=59 | | 3x-5÷3=x-3 | | q-1/7=-2/4 | | 12/5=y/8 | | p+1/8=2/8 | | 9*5-5/5=x | | 6q= 2 | | 5b-3=-2-10b | | 1+x=-2-2x | | 80x+30=75x-20 | | 34m=17 | | 9x5-5/5=X | | 4/8n-8-1/3n=7 | | 0.7w-0.5w+0.3w=2 | | −5x^2+10=30 | | x/4+1=0 | | 5k+6-6k=-1 | | −5x2+10=30 | | 14b+41=51 | | 8x+2009=4x+300 | | -17d–-2d+-20=10 | | -8x+2x=30 | | 250(0.2)+(0.25x)=(250+x)(0.3) | | n+n–1=3 | | -16d+17d=6 | | (9*x)(1+x)=0 | | 3r-4=7r |

Equations solver categories